Gas phase selective conversion of glycerol to acrolein over supported silicotungstic acid catalyst - Talebian-Kiakalaieh, A. (Korean Society of Industrial Engineering Chemistry, 2016)
Gas phase dehydration of glycerol to acrolein over a series of supported HSiW on ZrO2 and nano-sized γ-Al2O3 catalyst has been investigated. The characterization results revealed that impregnation of γ-Al2O3 nanoparticles increased the specific surface area, pore diameter, and thermal stability of the supported catalysts. The highest acrolein selectivity of 88.5% at 97.0% glycerol conversion was achieved over 0.5g 30HZ-20A catalyst in 3h at glycerol feed concentration of 10wt%, temperature=300 ?C and TOF=136 h-1. The coke deposition has no significant effect on the activity of 30HZ-20A catalyst. Indeed, the catalyst was stable even after 40h.